The Manifestation Of Religious Moderation As A Middle Way To Face Left And Right Extremism Within The Scope Of State Islamic Religious University - Ainiyah, Nur (Moderatio: Jurnal Moderasi Beragama, 2024)
Abstract: This paper aims to discuss the manifestation of religious moderation as a middle way to deal with left-wing (liberalism) and right-wing (radicalism) extremism within the scope of the State Islamic Religious University (PTKIN). This study emphasizes a qualitative approach with analytical-descriptive studies. The results and discussion of this study show that the concept of religious moderation requires religious people to be more inclusive (open) and not exclusive (closed). Religious moderation is not only an effort to mediate groups that are radical or extreme right, but also our efforts to mediate those who are liberal or extreme left. PTKIN as a forum for Islamic education under the auspices of the Ministry of Religion has an important role in giving birth to a moderate and tolerant young generation with a complex understanding of multiculturalism. Therefore, the manifestation of moderation in religion within the scope of PTKIN in the form of Religious Moderation Houses, religious courses, and the real role (realization) of religious moderation for each individual can lead us to the middle path to face left-right extremism within the scope of PTKIN as well as strengthen the concept of religious moderation that has been built. These aspects can channel us to harmony and harmony in the midst of diversity and diversity within the scope of PTKIN, even wider than that. The existence of this research is expected to be able to make academics and research to develop more widely related to the manifestation of religious moderation in all its forms and efforts, so as to give rise to new innovations to strengthen religious moderation in Indonesia.